Culture and development in the new media ecology: Filosofighters', case study, the Superinteressante transmedia newsgame - Bressan, Danilo [UNESP] (Univ Santiago Compostela, 2020)
With the arrival of the internet in the 1990s, the communication dynamics changed significantly. With the evolution of mobile technologies, the maturation of web 2.0 and the speed and protagonism of unlimited and broadband internet, the current scenario of the communication market, also due to media convergence, is becoming increasingly conducive to experimentation and development of innovative communication products. There is currently a need to meet the demands and new experiences of specific audiences. In this sense, the objective of this paper is to verify how newsgames can be used in journalism and to understand how the language of games is appropriately used in informative product content. After a theoretical reflection on the terms serious games and newsgames, transmedia products and their potential to be a new journalistic format, a case study of the Brazilian transmedia product Filosofighters is developed, developed by Superinteressante magazine.
Keywords: Media Ecology; serious game; newsgame; transmedia